ZTI-01 (fosfomycin for injection) in the treatment of hospitalized patients with complicated urinary tract infections. (8th March 2019) - Burgos, Rodrigo M; Rodvold, Keith A
Fosfomycin is a bactericidal antibiotic available since the 1970s whose intravenous formulation has been available in many countries outside the USA. Given the rise in drug-resistant bacteria, its introduction into the US market has become a necessity for addressing these organisms. This review provides an overview of the microbiology, clinical pharmacology and initial clinical experiences of the intravenous fosfomycin product (ZTI-01) that is undergoing clinical development in the USA for the treatment of complicated urinary tract infections and acute pyelonephritis.